TINGKAT KERENTANAN ABRASI DI PESISIR KABUPATEN PADANG PARIAMAN MENGGUNAKAN METODE COASTAL VULNERABILITY INDEX (CVI) - Rauda tul Husna; Helfia Edial (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
This abrasion vulnerability analysis was carried out on the coast of Kabupaten Padang Pariaman. The study aims to analyze the level of vulnerability of the coastal region of Kabupaten Padang Pariaman to the danger of abrasion. The research method was conducted using remote sensing and geographic information systems. Weighting parameters use the vulnerability index parameter (Coastal Vulnerability Index / CVI). The parameters of the vulnerability index (Coastal Vulnerability Index / CVI) used in this study are, wave parameters, beach slope, geomorphology, average sea level, tides, changes in coastline, and land use. The results obtained by the CVI value of the Padang Pariaman Coastal Area 5 categories, namely: very high vulnerability (> 58.36) in the Katapiang and Pasir high vulnerability (49.11 - 58.36) in Desa Gasan Gadang, moderate vulnerability (39.87 - 49.11) in Desa Sunua, Tapakis and Ulakan, low vulnerability (30.62 - 39.87) is found in Desa Pilubang, Koto Tinggi Kuranji Hilir, Malai V Suku and Padang Birik-Birik, and very low vulnerability (21.38 - 30.62) found in Desa Guguak Kuranji Hilir. The CVI value is obtained from the calculation of each weight parameter for the coastal abrasion vulnerability index. Areas with very high to high vulnerability are found in areas with land use dominated by settlements and fields and large coastline changes from 4.67 m / year.